Reflections on the production and use of interviews as a learning tool in educational podcasts for medical undergraduates - S. James; T. Awolesi; S. De Souza (European Psychiatry, 2022)
Introduction The therapeutic interview is one of the cornerstones of psychiatric practice. When practitioners are skilled in the art of interviewing, patients are allowed to share their narratives and explore their emotions, while the clinician can diagnose and treat more effectively. Discussions with colleagues can be used to share knowledge and experience. As part of a student project undertaken in Summer 2021, two students were tasked with producing a series of educational podcasts to be used for psychiatric training. Both students chose to complete several interviews with professionals in psychiatry. In this study, they will reflect on the efficacy of interviews as a learning tool, their experiences of podcast interviewing, and the transferable skills that they learned.